Optimation of Social Assistance Recipient Determination Using K-Means Clustering Algorithm and K-Nearest Neighbour Algorithm - Prakarsa, Graha; Rahadiyanti, Nira; Nursyanti, Reni; Hadiantini, Ratih (Sainteks: Jurnal Sain dan Teknik, 2025)
Determining the status of the family as recipients of assistance is very important, so that aid can be distributed accurately. Data mining takes advantage of experience or even mistakes in the past to add quality based on examples as well as the results of the analysis, one of which uses the capabilities of data mining techniques, namely clustering & classification. The purpose of this research is to determine the right beneficiaries. K-Means Clustering and K-Nearest Neighbor are 2 data mining problem solving algorithms used in selecting beneficiaries. Both of these troubleshooting algorithms make good performance. However, to be widely used, it is necessary to research which algorithm has higher accuracy. Based on this, in this study a comparison of the K-Means Clustering and K-Nearest Neighbor algorithms was carried out on the problem of selecting beneficiaries. Comparisons were made using 1760 data. Based on the tests that have been carried out, beneficiaries using k-means clustering got as much as 65.145% while K-Nearest Neighbor as much as 99.6501%. This shows that the K-Nearest Neighbor problem solving algorithm has higher accuracy.